The age of extremes: concentrated affluence and poverty in the twenty-first century. - Massey, Douglas S. (Demography, 1996)
The text of the presidential address delivered at the annual meetings of the Population Association of America in New Orleans, Louisiana, is presented. The writer argues that rising income inequality, urbanization, and increasing class segregation have produced a geographic concentration of poverty and affluence throughout the world, generating a radical change in the geographic basis of human society. He contends that the exposure of the world's poor to crime, disease, violence, and family disruption will increase as the density of poverty in the environment of the poor rises. He argues that the benefits and privileges of the wealthy, on the other hand, will be improved by the spatial concentration of affluence. He concludes that in the 21st century, the advantages and disadvantages of an individual's class position will be reinforced and compounded through ecological mechanisms that are made possible by the geographic concentration of poverty and affluence, leading to a profoundly divided and increasingly violent social world.